2020
DOI: 10.1155/2020/9094047
|View full text |Cite
|
Sign up to set email alerts
|

Health Conditions, Access to Care, Mental Health, and Wellness Behaviors in Lesbian, Gay, Bisexual, and Transgender Adults

Abstract: This study examined relationships among wellness behaviors, physical health conditions, mental health, health insurance, and access to care among a sample of 317 lesbian, gay, bisexual, and transgender (LGBT) adults. Participants completed a web-administered survey from May 2013 to April 2014. Of the sample, 41.6% of the participants reported having one or more health conditions. Most participants (92.1%) reported access to a health care facility and current health insurance coverage (84.9%), though 24.9% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The lack of significant moderation in this study can be potentially explained by two rationales: (1) the small sample size of sexual minority populations in this study made the moderation relatively undetectable and (2) probable depression was a robust predictor on its own toward predicting low health coverage, which could potentially mask the effect of sexual orientation. Nonetheless, sexual minorities still suffer from disproportionate mental health burden and health care coverage gaps according to the previous studies and the results from this study [ 2 , 12 , 22 , 23 , 33 ]. According to the BMHSU model, health care coverage is an enabling factor for addressing health care needs.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The lack of significant moderation in this study can be potentially explained by two rationales: (1) the small sample size of sexual minority populations in this study made the moderation relatively undetectable and (2) probable depression was a robust predictor on its own toward predicting low health coverage, which could potentially mask the effect of sexual orientation. Nonetheless, sexual minorities still suffer from disproportionate mental health burden and health care coverage gaps according to the previous studies and the results from this study [ 2 , 12 , 22 , 23 , 33 ]. According to the BMHSU model, health care coverage is an enabling factor for addressing health care needs.…”
Section: Discussionsupporting
confidence: 62%
“…Participants were divided into two groups: (1) those who were insured and had not experienced unaffordable medical costs (“high coverage”) and (2) those who were either insured or uninsured but had experienced unaffordable medical costs (“low coverage”). The rationale behind combining these two variables was that health insurance status alone rarely explains its association with mental illness, and previous research found that difficulty of paying copayment did exist among insured LGB populations [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with higher education may have better access to care and the ability to pay for care, which is important to note given historical barriers encountered by SM individuals in accessing care. These healthcare barriers among SM individuals and the larger SGM population have been well documented (Henry et al, 2020; Martos et al, 2018, 2019) and have resulted in unmet care needs (Fish et al, 2021; Wolstein et al, 2018). Having the financial ability to seek and obtain the care needed may reduce health disparities among some SGM populations (Gonzales et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Heath et al's (2013) model noted that individuals receiving collaborative care are more likely to be managing symptoms of potential mental and physical health conditions and, thus less likely to be impacting their wellness.Lastly, higher proportions of individuals from the LGBTQIA + community were represented in pro les with lower wellness scores. Previous scholars noted that the LGBTQIA + community is more likely to receive reactive services for their wellness and less likely to nd competent providers to manage their unique presenting concerns(Henry et al, 2020;Moe, 2016). For example, Moe (2016) completed a metaanalysis of 25 studies examining the wellness of individuals from the LGBTQIA + community and concluded that wellness scores tend to be lower than non-sexual minority individuals.…”
mentioning
confidence: 99%